Correlation of axial length and myopic macular degeneration to levels of molecular factors in the aqueous - Wong, Chee Wai; Yanagi, Yasuo; Jonas, Jost B. (Scientific reports, 2019)
To elucidate the molecular processes associated with the development of myopic macular degeneration (MMD), we measured the intraocular concentrations of molecular factors in emmetropic and myopic eyes. This is a retrospective clinic-based case-control study that included eyes undergoing routine cataract surgery whereby aqueous humour samples were obtained. We measured the concentrations of pigment epithelium derived factor(PEDF), matrix metalloproteinase 2(MMP-2), tissue inhibitor of metalloproteinase(TIMP-2), vascular endothelial growth factor isoform A(VEGF-A), interleukin 8(IL-8), interleukin 6(IL-6), C-reactive protein(CRP), angiopoietin 2(Ang2), and amphiregulin. 38 eyes (axial length (AL): 22.4-32.4 mm), including 12 highly myopic (HM) eyes (AL ≥ 26.5 mm) without MMD and 12 HM eyes with MMD but without neovascularization were included. Eyes with MMD were found to have significantly lower VEGF-A levels (p = 0.007) and higher MMP-2 levels (p = 0.02) than control eyes after adjusting for age and gender. MMP-2 levels correlated positively (r = 0.58, p = 0.002), while VEGF-A levels correlated negatively with longer axial length (r = −0.75, p < 0.001). Both the concentrations of VEGF-A (P = 0.25) and MMP-2 (P = 0.69) were not significantly associated with MMD after adjusting for AL. These findings suggest that the predominant mechanism underlying the development of non-neovascular MMD may be axial elongation, driven in part by MMP-2 related mechanisms.